The effect of the euro on export patterns: Empirical evidence from industry data - Gavin Murphy; Iulia Siedschlag (The Economic and Social Research Institute (ESRI), 2008)
We estimate the euro effect on Irish export patterns using a panel of industry data over the period 1993-2004. Our innovation is to account for country and industry specific omitted trending variables bias. We find that the euro effect on Irish exports to the euro area countries relative to the rest of the trading partners of Ireland has been positive, significant and increasing since 2000. Furthermore, we find heterogeneous euro effects across industries. We find consistent significant positive euro effects for industries characterised by increasing returns to scale.
Keywords: F14; F15; F41; 330; EMU; trade; Ireland; Europäische Wirtschafts- und Währungsunion; Euro; Außenwirtschaft; Export; Industrie; Skalenertrag; Irland